2015
DOI: 10.1063/1.4923382
|View full text |Cite
|
Sign up to set email alerts
|

Vertically aligned dust particles under the influence of crossed electric and magnetic fields in the sheath of a radio frequency discharge

Abstract: We present experiments on two dust particles with a size of a few microns that are levitated in the sheath region of an rf discharge in the presence of an external magnetic field transverse to the sheath electric field. The two particles are vertically aligned due to the ion focusing effect. First, it is observed that the magnetic field causes a displacement of the dust particles either in the E→×B→- or in the opposite direction. Second, at a sufficiently large neutral gas pressure, the vertical alignment brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Further, the influence on vertically aligned dust particles is studied. It is found that the ion wake that is responsible for the vertical alignment is destroyed and that the vertical alignment is easily broken by the magnetic field [2].…”
mentioning
confidence: 99%
“…Further, the influence on vertically aligned dust particles is studied. It is found that the ion wake that is responsible for the vertical alignment is destroyed and that the vertical alignment is easily broken by the magnetic field [2].…”
mentioning
confidence: 99%
“…parallel to the electrodes. There, one finds a quite complex reaction of the dust particles even at relatively small fields [214][215][216][217]. Vertically the dust is trapped by the force balance of electric field force and gravity Q d E z =m d g, as discussed above.…”
Section: Sideways Motionmentioning
confidence: 93%
“…At further increased field the particles start to move back to the original position along the   E B direction, see figure 14(b). The sideways motion of the dust strongly depends on the particle size as well as the gas pressure [215][216][217].…”
Section: Sideways Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar situation with dust particles in the magnetic field suspended near the electrode layer of the RF discharge also moved in the direction opposite to the E × B drift. [24][25][26] In the works of Barnat, [27] the properties of RF discharge in a perpendicular magnetic field were investigated. It should also mention the theoretical study [28][29][30][31][32] of the influence of weak transverse/longitudinal magnetic fields on the dynamics of dust structures.…”
Section: Introductionmentioning
confidence: 99%